KEEFEKTIFAN KALIMAT DALAM TEKS BIOGRAFI SISWA KELAS X SMA NEGERI 1 RANAH PESISIR - Lasmi Septiani; Yulianti Rasyid (EDU RESEARCH, 2025)
This study aims to describe the effectiveness of sentences in biographical texts written by grade X students of SMA Negeri 1 Ranah Pesisir. The focus of the study was on three main indicators of effective sentences, namely word economy, word standardization, and spelling usage (capital letters, periods, and commas). This study used a qualitative approach with a descriptive method. Data in the form of sentences in biographical texts written by 30 students were analyzed using documentation techniques and triangulation of data validity. The results showed that out of 303 sentences analyzed, there were 192 effective sentences and 111 ineffective sentences. Reviewed from the aspect of word economy, 86 sentences were considered appropriate and 25 sentences were inappropriate. From the aspect of word standardization, only 38 sentences were appropriate, while 73 sentences were inappropriate. Meanwhile, in terms of spelling usage, correct capitalization was found in 55 sentences, correct use of periods in 100 sentences, and correct use of commas in 93 sentences.